A critical review of incremental sheet forming in view of process parameters and process output. Issue 2 (3rd April 2022) - Magdum, Rohit A.; Chinnaiyan, Pandivelan
ABSTRACT: This paper presents a detailed review of incremental sheet forming (ISF). The first part presents an introduction to the ISF technology based on the working principles, different variants of the technology, process parameters and process outputs commonly studied. New trends in ISF like hot forming, multi-point tool forming have been reviewed in detail. In this paper, the effect of different process parameters on the output responses are thoroughly reviewed. Moreover, existing literatures related to outputs like forming forces, geometric accuracy, surface finish and formability in ISF are studied and literature gaps are interpreted. Finally, concluding remarks on the literature gap identified from this review will provide the foundation to the researchers for future work.